Utilização do Geogebra na resolução de problemas contextualizados: uma proposta para o ensino de matrizes - CASTRO, Adriane do Socorro Pires (2022)
The present work consists of proposing a differentiated activity to the traditional teaching of matrices based on the use of digital technologies. It was sought to promote, from the use of GeoGebra software in solving contextualized problems, an improvement in the process of teaching matrices for students from two classes of the third year of high school in the public school system in the city of Acará/PA. With a quantitative-qualitative approach and of a descriptive nature, two questionnaires were used for the students, one for diagnosis and the other for evaluation, and a questionnaire directed to the welcoming teacher. The research results showed that it is possible to promote the use of digital technologies in the classroom combined with contextualized problems to assist in the understanding of mathematical concepts, providing a more meaningful learning for students.